Nimby e a produção democrática do espaço urbano: o caso da cidade Matarazzo no município de São Paulo – SP/Brasil - Freitas, Helmo Franklin Alves de (2022)
Many real estate projects capable of impacting the urban environment generate situations of conflicts between the interests of the local population and real estate capital. In this context, it is part of what has been called in the academic literature as nimby effect, acronym in English for "not in my backyard". According to the specialized literature the NIMBY phenomenon can be interpreted according to two antagonistic viewpoints. The first is a misrepresentation of the democratic process and aims to safeguard the interests of certain social classes to the detriment of collective interests. The second, on the other hand, is a legitimate democratic process that, through popular participation, seeks to protect collective interests against the interests of capital that profit with the production and reduction of urban space. As an example of a conflicting situation between the local population and a real estate development, the issue of the Matarazzo City Project can be cited in the central region of the city of São Paulo/SP-Brazil. This project had architectural interventions in the area of the former Matarazzo Hospital, including the creation of an underground passage for vehicles on a stretch of Rua São Carlos do Pinhal between Alameda Rio Claro and Rua Itapeva, and which promised an integration between this environment and people passing through the region, including Av. Paulista, as well as foresaw the construction of a small Oasis and a living space open to all. The proposal to build this underpass resulted in a judicial process by the associations of neighborhood residents, AMACON - Association of residents of the neighborhood of Consolação and adjacencies and AMORBELA - Association union of residents of the neighborhood of Bela Vista & Bixiga, which eventually made it impossible. Therefore, starting from the hypothesis that such a situation constitutes an expression of the NIMBY phenomenon, this dissertation will aim to analyze the issue of the conflict between these associations and the project of construction of the underground passage provided for by the Cidade Matarazzo enterprise in the central region of the city of São Paulo/SP-Brazil, with ways to answer the following research question: what elements can be identified in the conflict mentioned and to show that the reaction of the local population reflected exclusively particular interests or, on the contrary, to point out that such a reaction was a legitimate manifestation of the democratic exercise of production of local urban space? This is an exploratory study based on bibliographic survey, documentary analysis and field reconnaissance activities. It is expected that the results can bring elements of elucidation about the conflicting issue generated, as well as contributing to future studies and urban projects, whether private or public initiative, and aimed at reconciling the production of urban space, popular participation and democracy.